A STUDY ON CONSUMER BEHAVIOUR TOWARDS BRANDED UPS IN TIRUPATTUR TOWN (International Journal of Scientific Research and Management (IJSRM), 2017)
scenario, Organizations are facing heavy competition in attracting and retaining their customers because the buyer’s behaviours are habitually changed and also buyer’s psychology is highly unpredictable. The reason is so many factors are influenced while they taking any purchasing decision. The deciding factors like brand name, physical appearance of the product, price, and promotional aspects, after sales service, availability of the product and various offers are playing a vital role in purchasing decisions of the buyer.